Kemampuan Komunikasi, Kolaborasi, Metakognisi, dan Hasil Belajar Mata Pelajaran Operasi Teknik Kimia - Artanti, Reni Ratih; Rijanto, Tri (Jurnal Pendidikan Madrasah, 2024)
This study aims to analyse the relationship between communication skills, collaboration, and metacognition to student learning outcomes in the subject of Chemical Engineering Operations. Communication skills refer to students' skills in conveying ideas, discussing, and understanding concepts through verbal and nonverbal interactions. Collaboration includes student cooperation in solving chemical engineering problems as a team, while metacognition refers to students' awareness of the thinking process and learning strategies used. Learning outcomes are measured through students' conceptual understanding and practical skills in completing chemical engineering operational tasks, such as process calculations, system analysis, and operational efficiency evaluations. The study uses a quantitative method with a correlational approach to measure the influence of these variables on learning outcomes. The research sample consisted of students in the Chemical Engineering class at SMK Negeri Ngasem, with a total of 100 respondents who were randomly selected. Data was collected through learning outcome tests, observation sheets, questionnaires, and interviews. The results of the analysis showed that communication skills, collaboration, and metacognition had a significant influence on student learning outcomes. Collaboration and metacognition skills make a more dominant contribution than communication. This study concludes that improving communication, collaboration, and metacognition skills in an integrated manner can improve student learning outcomes in the subject of Chemical Engineering Operations. Thus, it is recommended that educators integrate active learning strategies that focus on group discussions, problem-based learning, and metacognitive reflection to support more effective learning.